An Empirical Research on the Job Satisfaction and Job Performance of Rice Mill Workers - ROBERT. P, WILLIAM; G, PRAVEEN. (The journal of contemporary issues in business and government, 2020)
The research paper titled the relationship between Job Satisfaction and Job Performance. This paper studies factor influencing Job Satisfaction toward Job Performance. Descriptive research is applied using convenience method of sampling with 71 respondents. The data is collected from the Rice Mill workers. The majority of respondents were Male and their majority of Age group were36-25 years. The tools used of the study is mean analysis, frequency analysis, t-test, ANOVA and Regression. Through analysis it is found that there is no significant difference between the Job Satisfaction and Job Performance because of the improper working of machineries and lack of technologies in Rice mill Sector.